Regression discontinuity designs : theory and applications - Hill, R. Carter; Fomby, Thomas B.; Escanciano, Juan Carlos; Hillebrand, Eric; Jeliazkov, Ivan, 1973-; Cattaneo, Matias D. (Bingley : Emerald Publishing Limited, 2017)
The Regression Discontinuity (RD) design is one of the most popular and credible research designs for program evaluation and causal inference. This volume 38 of Advances in Econometrics collects twelve innovative and thought-provoking contributions to the RD literature, covering a wide range of methodological and practical topics. Some chapters touch on foundational methodological issues such as identification, interpretation, implementation, falsification testing, estimation and inference, while others focus on more recent and related topics such as identification and interpretation in a discontinuity-in-density framework, empirical structural estimation, comparative RD methods, and extrapolation. These chapters not only give new insights for current methodological and empirical research, but also provide new bases and frameworks for future work in this area. This volume contributes to the rapidly expanding RD literature by bringing together theoretical and applied econometricians, statisticians, and social, behavioural and biomedical scientists, in the hope that these interactions will further spark innovative practical developments in this important and active research area.
Prelims -- On interpreting the regression discontinuity design as a local experiment -- Identification and estimation using a density discontinuity approach -- The deterrence effect of prison : dynamic theory and evidence -- An overview of geographically discontinuous treatment assignments with an application to children's health insurance -- External and internal validity of a geographic quasi-experiment embedded in a cluster-randomized experiment -- The comparative regression discontinuity (CRD) design : an overview and demonstration of its performance relative to basic RD and the randomized experiment -- Party bias in union representation elections : testing for manipulation in the regression discontinuity design when the running variable is discrete -- Testing stability of regression discontinuity models -- Regression kink design : theory and practice -- Regression discontinuity designs with clustered data -- Bootstrap confidence intervals for sharp regression discontinuity designs -- The devil is in the tails : regression discontinuity design with measurement error in the assignment variable -- Index.
Includes index.
Print version record
Keywords: Regression analysis; Economics -- Statistical methods; Business & Economics -- Economics -- Macroeconomics; Econometrics